Dendrohydroclimate reconstructions of July–August runoff for two nival‐regime rivers in west central British Columbia. Issue 3 (19th March 2012) - Starheim, Colette C. A.; Smith, Dan J.; Prowse, Terry D.
Abstract: Lengthy records of river discharge are necessary to comprehensively assess the long‐term connection between synoptic climate forcings and nival‐regime systems in British Columbia. A regional multispecies network of tree‐ring width and ring density chronologies was built for west central British Columbia with the intention of dendrohydrologically extending short runoff records in this area. Extended records of July–August mean discharge anomalies for the Skeena and Atnarko Rivers were reconstructed back toad 1660. Low flow events represented during the late 1600s, early 1700s and late 1800s lie beyond those experienced during the recent instrumental period for these basins. The documentation of extreme events of this magnitude necessitates consideration when planning for future water resources in this region. Supplementary dendroclimatic reconstructions of the winter Pacific North American (PNA) pressure anomaly pattern and records of mean summer temperature and end‐of‐winter snow water equivalent were also constructed. These ancillary climate records provide insight into the long‐term climate drivers of annual discharge dynamics within these nival basins. Correlation and wavelet analyses confirm the persistent relationship of synoptic climate regimes described by the Southern Oscillation Index, NINO 3.4, Pacific Decadal Oscillation and PNA indices on runoff in west central British Columbia. Copyright © 2012 John Wiley & Sons, Ltd.